AYURVEDIC MANAGEMENT OF THROMBOANGIITIS OBLITERANS (TAO) WITH MANJISHTADI KSHARABASTI IN VATARAKTA: A CASE STUDY - Bibhuti, Kumari Nidhi Shree; Pathak, Avnish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The complex interplay of thromboangiitis obliterans (TAO) with the Ayurvedic perspective of Vatarakta presents a multifaceted area of study, particularly in exploring the therapeutic potential of Manjishtadi Ksharabasti. A comprehensive examination reveals that TAO, characterized by segmental vasculitis, primarily affects young males who are habitual users of tobacco, resulting in ischemic events and potential limb loss if not properly managed (Stephen V Faraone et al., 2021). In traditional Ayurvedic literature, Vatarakta embodies a condition related to the aggravation of Vata dosha and the accumulation of toxins, or ama, in the body, leading to disturbances in the microcirculation. This study aims to bridge the gap between contemporary medical understanding and ancient Ayurvedic practices, proposing that principles from Ayurveda can contribute significantly to the management of TAO through targeted therapies such as Manjishtadi Ksharabasti, an enema enhanced with herbs known for their detoxifying properties. The integration of Ayurvedic management, particularly through the lens of Manjishtadi Ksharabasti, represents a promising frontier in addressing the multifactorial aspects of thromboangiitis obliterans. By elucidating the connections between Ayurvedic theory and modern therapeutic needs, this study encourages a reevaluation of treatment paradigms, advocating for a fusion of wisdom from ancient texts with contemporary medical practices.